Analisis Keterampilan Teknik Dasar Renang Gaya Dada - Emeilda Riska Tama; Maidarman - (Jurusan Kepelatihan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2019)
The problem in this study is the low mastery of the breaststroke swimming technique of UNP FIK coaching students. The purpose of this study was to determine the level of mastery of breaststroke swimming techniques students majoring in FIK UNP coaching. This type of research is descriptive. Place of research carried out at the FIK UNP swimming pool. The population in this study were students of FIK Padang State University of Padang Department of Training who took the deepening swimming course in the July-December 2019 semester of 40 people. Sampling was done by purposive sampling technique, the number of samples in this study were 21 students. The instrument in this study used the format of assessment of breaststroke swimming technique analysis. Data analysis techniques using descriptive percentages. The results obtained data (1) assessment of body position at a good level. (2) Mastery of hand movement techniques at a good level. (3) Mastery of leg movement techniques at a good level. (4) Mastery of breathing at a good level. (5) Mastery of motion coordination at a good level. Basic breaststroke swimming technique skills at a good level